Z39.50 Standard for information search and retrieval - Darwish, Wessam (Cybrarians Journal, 2004)
This research paper provides a brief historical and introductory overview of the standard (Z39.50) with a presentation of the capabilities and services provided by this standard in its third edition. It then explains the importance of this standard in various library applications in general, then briefly presents the advantages and disadvantages of this standard, and finally it reviews The expected future of this standard in terms of issuing a revision to the third version, issuing the next generation of this standard (ZING), and reviewing and developing the fourth version of this standard.